The The effect of assembled diffuser diameter on water quality and growth performance of Nile tilapia (Oreochromis niloticus) - Anjarkasi, Hias; Dewantoro, Eko; Lestari, Tuti Puji (Universitas Malikussaleh, 2025)
Nile tilapia (Oreochromis niloticus) is one of the leading aquaculture commodities in Indonesia, valued for its high economic potential and growing market demand. The success of tilapia farming is highly influenced by optimal water quality, particularly the level of dissolved oxygen (DO), which plays a crucial role in supporting the metabolic and physiological processes of the fish. One commonly used technology to maintain DO levels is the diffusion aerator system, whose efficiency is strongly affected by the design and diameter of the diffuser. This study aimed to analyze the effect of diffuser diameter variation on water quality and tilapia growth performance, and to determine the most effective diameter for maintaining optimal rearing conditions. The experiment was conducted over 45 days using a completely randomized design (CRD) consisting of six treatments and three replications: (A) stone aerator (control), and custom-made diffusers constructed from used tires with diameters of (B) 1 inch, (C) 2 inches, (D) 3 inches, (E) 4 inches, and (F) 5 inches. Observed water quality parameters included temperature, pH, DO, ammonia, nitrite, and alkalinity. Growth performance indicators measured included specific growth rate (SGR), daily feed intake, feed conversion ratio (FCR), and survival rate. The results indicated that all treatments-maintained water quality within optimal ranges for tilapia culture. However, no significant differences (p > 0.05) were observed in growth performance across treatments. These findings suggest that tire-based diffusers can serve as effective, economical, and environmentally friendly alternatives to conventional aeration systems in tilapia aquaculture. Keywords: Aeration; Aquaculture; Assembled Diffuser; Fish Growth; Nile Tilapia; Water Quality